Adaptação cultural e validação da escala de Wexner em mulheres com incontinência anal na população brasileira - Mariana Furtado Meinberg (2014)
Introduction: The aim of this study was to validate the Portuguese version of the Wexner Score for Anal Incontinence in the brazilian population. Metodology: The english version was translated to portuguese by two independent translators and then establisehd a final portuguese version. The internal consistency of the questionnaire was evaluated in 50 patients by test retest reliability, with a 15-days gap between interviews. The convergente validity of the questionnaire was performed by the comparison of the Wexner Score with another questionanaire of quality of life, the FIQL score. Results: The answers to both questionnaires at the test retesting showed signifincant correlation by Wilcoxon test. The p=0,354 demonstrated that the median of both scores are statistically equals. The Cronbachs Alphas value for the translated version was 0,932, showing a high level of internal consistency. A high level of internal consistency was also existente, when each iten of the questionnaire was evaluated separately. The analysis of the convergent validity of the portuguese version showed significant relation when compared to the total score of the FIQL questionnaire by the Spearmans correlation. Conclusion: The proposed questionnaire was well accepted by the population for its ease of understanding and for its limited number of itens that can be rapidly answered. In conclusion, this study demonstrated the linguistic and psychometric validity of the postuguese version of the Wexner Score for the brazilian population..